The relationship of arrhythmias with structural and functional heart changes according to the echocardiography data in the adult population of the Arctic - E. V. Zatonskaya; G. V. Matyushin; N. G. Gogolashvili; N. Ya. Novgorodtseva (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To study the relationship of arrhythmias, registered by the electrocardiography (ECG) and ECG Holter monitoring, with the changes of the heart and disorders of its function detected by echocardiography in the adult population of the Arctic, living in unfavorable environmental conditions.Material and methods. Patients (n=348) of both sexes, aged 20 years and older, were randomly selected and examined. All participants were carried out ECG recording in 12 standard leads, Holter monitoring and transthoracic echocardiography.Results. Statistically significant associations between certain types of arrhythmias and echocardiographic changes were observed. There were revealed correlations of medium strength: between atrial fibrillation (AF), registered by ECG and dilatation of the left (r=0.3215) and right (r=0.3275) atrium; between AF, registered by Holter monitoring, and left ventricular (LV) systolic dysfunction (r=0.3216); between premature ventricular contractions, registered by Holter monitoring, and LV hypertrophy (r=0.3332).Conclusion. The аassociation between arrhythmias and structural and functional changes of the heart in individuals living in adverse climatic conditions were confirmed.